Differential Placental DNA Methylation of NR3C1 in Extremely Preterm Infants With Poorer Neurological Functioning - van Dokkum, Nienke H.; Bachini, Sofia; Verkaik-Schakel, Rikst Nynke; Baptist, Dyvonne H.; Salavati, Sahar; Kraft, Karianne E.; Scherjon, Sicco A.; Bos, Arend F.; Plösch, Torsten (Frontiers in Pediatrics, 2022)
Background: Understanding underlying mechanisms of neurodevelopmental impairment following preterm birth may enhance opportunities for targeted interventions. We aimed to assess whether placental DNA methylation of selected genes affected early neurological functioning in preterm infants. Methods: We included 43 infants, with gestational age < 30 weeks and/or birth weight < 1,000 grams and placental samples at birth. We selected genes based on their associations with several prenatal conditions that may be related to poor neurodevelopmental outcomes. We determined DNA methylation using pyrosequencing, and neurological functioning at three months post-term using Prechtl’s General Movement Assessment, including the Motor Optimality Score – Revised (MOS-R). Results: Twenty-four infants had atypical MOS-R, 19 infants had near-optimal MOS-R. We identified differences in average methylation of NR3C1 (encoding for the glucocorticoid receptor) (3.3% [95%-CI: 2.4%-3.9%] for near-optimal versus 2.3% [95%-CI: 1.7%-3.0%], p=0.008 for atypical), and at three of the five individual CpG-sites. For EPO, SLC6A3, TLR4, VEGFA, LEP and HSD11B2 we found no differences between the groups. Conclusion: Hypomethylation of NR3C1 in placental tissue is associated with poorer neurological functioning at three months post-term in extremely preterm infants. Alleviating stress during pregnancy and its impact on preterm infants and their neurodevelopmental outcomes should be further investigated.